Enoplognatha bryjai new species, a bizzare cobweb spider of the Pannonian swamps (Araneae, Theridiidae) - Řezáč, Milan; Řezáčová, Veronika; Heneberg, Petr (Zootaxa, 2016)
During faunistic research of reed beds associated with lakes in the Pannonian region of Czechia we found an Enoplognatha species with spectacular morphology of the male chelicerae. Despite this species being found in an arachnologically well researched area, and that the European species of the genus Enoplognatha have been recently revised (Bosmans & Van Keer 1999), it appears to be a new species.